2010
DOI: 10.1080/00223980903356099
|View full text |Cite
|
Sign up to set email alerts
|

Siblings' Motives for Talking to Each Other

Abstract: The sibling relationship is an involuntary one that individuals often maintain throughout life (V. G. Cicirelli, 1995; M. A. Fitzpatrick & D. M. Badzinski, 1994; P. Noller & M. A. Fitzpatrick, 1993). The authors investigated interpersonal communication motives in sibling relationships to examine the way in which siblings voluntarily maintain their relationships with one another over time. R. B. Rubin, E. M. Perse, and C. A. Barbato (1988) identified 6 primary motives that people have for communicating: affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(52 reference statements)
0
9
1
1
Order By: Relevance
“…More surprisingly was the finding that birth order had no impact on any of the six subscales of the LSRS. This contradicts previous research (e.g., Rocca et al, 2010) that showed that birth order can impact siblingships. Additionally, those with married parents believed there was more positively in the adult sibling relationships versus those with divorced parents.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…More surprisingly was the finding that birth order had no impact on any of the six subscales of the LSRS. This contradicts previous research (e.g., Rocca et al, 2010) that showed that birth order can impact siblingships. Additionally, those with married parents believed there was more positively in the adult sibling relationships versus those with divorced parents.…”
Section: Discussioncontrasting
confidence: 96%
“…They also found that first born children reported communicating more for control while the other birth order positions reported communicating for pleasure, inclusion, and relaxation (Rocca et al, 2010). It has been found that men who grew up with a sibling of the same sex are significantly more extraverted while women who grew up with a sibling of the same sex are significantly more conscientious (Szobiova, 2008;Tucker et al, 1997).…”
Section: The Importance Of the Sibling Dyad And Birth Ordermentioning
confidence: 99%
“…During early adolescence, siblings disclose to one another about a variety of topics, and with greater frequency, than to parents or friends, in particular when the relationship is warm, trusting, and supportive (Howe, Aquan-Assee, Bukowski, Lehoux, & Rinaldi, 2001;Howe, Aquan-Assee, Bukowski, Rinaldi, & Lehoux, 2000). Although peers become increasingly important during emerging adulthood, siblings still disclose to one another often (Dolgin & Lindsay, 1999), especially to seek support and convey affection (Rocca, Martin, & Dunleavy, 2010). Also, it is important to note that they report being just as willing to disclose their risky behaviors to siblings as to peers (Aldeis & Afifi, 2013).…”
Section: Self-disclosurementioning
confidence: 99%
“…More recent studies examining relational maintenance behaviors have continued to ignore the workplace. Although workplace relationships are considered to be interpersonal, the predominance of relational maintenance research has focused on nonworkplace relationships, such as friendships (Ledbetter, 2009), sibling relationships (Rocca, Martin, & Dunleavy, 2010), and Chory and Bandfield (2009) examined the relationship between media dependence and relational maintenance strategies between family, friends, and romantic partners. Given the continued focus on nonwork-related relationships, the current study buttressed the association between relational maintenance strategies involving friends, family, and relational partners and those that take place between coworkers.…”
Section: Relational Maintenance Strategiesmentioning
confidence: 99%